2023
DOI: 10.1063/5.0163641
|View full text |Cite
|
Sign up to set email alerts
|

Chiral molecule candidates for trapped ion spectroscopy byab initiocalculations: From state preparation to parity violation

Arie Landau,
Eduardus,
Doron Behar
et al.

Abstract: Parity non-conservation (PNC) due to the weak interaction is predicted to give rise to enantiomer dependent vibrational constants in chiral molecules, but the phenomenon has so far eluded experimental observation. The enhanced sensitivity of molecules to physics beyond the Standard Model (BSM) has led to substantial advances in molecular precision spectroscopy, and these may be applied to PNC searches as well. Specifically, trapped molecular ion experiments leverage the universality of trapping charged particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…On the other hand, it was demonstrated that an increased dodecapole potential generated in an asymmetric linear ion trap (LIT) [97] opens new pathways for exciting applications in mass spectrometry or Coulomb crystals. Such a setup also enables dark ion (inappropriate confined species) elimination from a trapped ion-chain consisting of physical qubits [47], or performing searches for time and parity violations that could constrain sources of new physics BSM [83,110,111].…”
Section: Of 36mentioning
confidence: 99%
“…On the other hand, it was demonstrated that an increased dodecapole potential generated in an asymmetric linear ion trap (LIT) [97] opens new pathways for exciting applications in mass spectrometry or Coulomb crystals. Such a setup also enables dark ion (inappropriate confined species) elimination from a trapped ion-chain consisting of physical qubits [47], or performing searches for time and parity violations that could constrain sources of new physics BSM [83,110,111].…”
Section: Of 36mentioning
confidence: 99%
“…Since such molecules have a neutral precursor, the molecular ion may be susceptible to predissociation in a vibrational spectroscopy experiment due to a low dissociation threshold. However, the two hydrogen isotopes in CHDBrI + give rise to a high dissociation threshold with a value of 1.29 eV as opposed to other halogenated methanes along with the high transition state energy between enantiomers of 1.3 eV, indicating that long lifetimes should be accessible for this candidate, 1 while tunneling effects should be negligible. Moreover, the proposed state preparation and detection methods for CHDBrI + through near-threshold, state-selective photo-ionization suggest that its preparation in an internally cold state is possible, improving the contrast in a future measurement.…”
mentioning
confidence: 98%
“…The latter system was proposed as a promising candidate for future high-precision laser spectroscopy experiments on trapped ions, due to a number of experimental advantages. 1 This proposal follows recent successful precision measurements on ionic systems, such as the molecular ion eEDM (electron electric dipole moment) measurement, 36 and quantum logic spectroscopy of molecular ions. 37,38…”
mentioning
confidence: 99%
See 2 more Smart Citations